MOCAPE: Two institutions – one envelope – one public space. Issue 2 (2nd May 2019) - Ruppert, Simon; Bollinger, Klaus; Grohmann, Manfred
Abstract: In 2007 the Austrian architectural firm Coop Himmelb(l)au won an international competition with its design idea for a monolithic, "slightly twisted" structure with a multifunctional façade. This design has been largely retained. The organization of the volumes and the urban planning positioning could also be essentially implemented. As a cultural centre, the building unites two independent institutions under one roof: the Museum of Contemporary Art (MOCA) and the Planning Exhibition (PE). Both institutions are housed in rectangular volumes under a covered plaza. Also included are community areas such as an auditorium, conference rooms, multifunctional exhibition halls and service areas. Ramps and escalators lead from the large entrance area to the main level at +10 m. This marks the starting point for tours of the museums. There is a silvery, shiny, softly shaped "cloud" in the centre which accommodates a café, bookstores and a museum shop. It also connects the exhibition rooms over several floors via bridges and ramps. The transparent façade highlights the main entrance and circulation zone between the two buildings and allows unobstructed views between the inside and outside. The open, column‐free exhibition areas with heights from 6 to 17 m also strengthen the impression of a generous design concept.